Unsaturated soil hydraulic conductivity (Kh) and soil resistance under different land uses of a small upstream watershed in Mt. Banahaw de Lucban, Philippines - Garcia, Ronald C.; Galang, Marco A. (2021)
"Soil hydraulic conductivity influences hydrologic processes and the ability of watersheds to provide ecosystem services. Like most soil properties, however, it is highly spatially variable at different scales due to biophysical and anthropogenic factors. To quantify spatial variability, the study assessed the influence of land use/land cover (LULC) on soil hydraulic conductivity and compaction, as reflected by soil resistance in a small upstream watershed. Compaction was measured using a soil compaction tester and the unsaturated soil hydraulic conductivity (Kh) was estimated in the field using the inverse auger hole method" - title page.
Includes bibliographical references.
Keywords: Hydrology -- Philippines -- Mount Banahaw de Lucban; Percolation; Soils -- Philippines -- Mount Banahaw de Lucban